Dynamics of epigenetic control on transgene expression mediated by lentivirus in mouse pluripotent stem cells - Alhaji, Suleiman Yusuf (2018)
Autologous transplantation of patient specific iPS-derived cells for ex vivo gene therapy application could be the only curative option for patients that do not have compatible donor. One of the limitations of successful gene therapy is short-lived duration of transgene expression in mammalian cells cause by DNA methylation. Pluripotent stem cells have shown to possess minimal genomic methylation profile. Therefore, it is hypothesized that improve durability of transgene expression could be achieved if the transgene is introduced into a cell while it is still in a pluripotent state. The aim of this study is to assess durability of transgene expression in mouse pluripotent stem (iPS and ES) cells transduce with lentivirus carrying GFP reporter gene driven by either human elongation factor (EF1) or cytomegalovirus (CMV) promoter and to dissect the factors that influence the duration of transgene expression in both cells. LV/EF1/GFP and LV/CMV/GFP transduced iPS cells exhibited significant GFP expression (>80% expressing cells) with persistent mean fluorescent intensity (MFI) through out the 30 days of the study period and beyond. In ES cells, LV driven by either EF1 or CMV promoter presented lower GFP expression (>50%) but surprisingly, LV/EF1/GFP showed significantly higher MFI when compared to LV/CMV/GFP. Analysis on the integrated copy of transgene in all transduced cells demonstrated similar copy number in the cells’ genome. Significant increase in GFP intensity following 5aza-C treatment was observed in ES cells, implicating the effect of DNA methylation in transgene silencing. However, this effect was not observed in transduced iPS cells. DNA methylation study showed that the transgene promoter and the GFP region of the provirus in ES cells had higher DNA methylation when compared to that of provirus in iPS cells. The transduced iPS cells were then induced to diffeentiate into hematopoietic stem cells (HSCs). The HSCs colony derived from the LV/EFI/GFP transduced iPS cells showed GFP+ cells of about 68.8%, while the LV/CMV/GFP transduced iPS-derived HSCs exhibited GFP+ cells of about 57.8%. This study demonstrated that, (1) persistent transgene expression mediated by LV carrying GFP driven by both EF1 and CMV has been observed in iPS cells. However, a significant decrease in GFP expression in ES cell was seen, (2) GFP expression in ES cells is affected by a transgene silencing mechanism and this phenomenon was not observed in iPS cells, and (3) both LV/EF1/GFP and LV/CMV/GFP transduced cells were able to generate HSCs upon directed differentiation and the cells retained considerable level of GFP expression. These findings could potentially be beneficial in the application of iPS-derived cells for prolonged therapeutic gene expression and could be translated in clinic for a persistent correction of genetic disorders using gene therapy technology in the future.